VARIATION IN LUNG VOLUMES AND CAPACITIES AMONG YOUNG MALES IN RELATION TO HEIGHT - Bhatti, Urooj; Rani, Keenjher; Memon, Muhammad Qasim (Journal of Ayub Medical College Abbottabad, 2014)
Background: Vital Capacity (VC) is defined as a change in volume of lung after maximal inspiration followed by maximal expiration is called Vital Capacity of lungs. It is the sum of tidal volume, inspiratory reserve volume and expiratory reserve volume. Vital capacity of normal adults ranges between 3 to 5 litres. A number of physiological factors like age, gender, height and ethnicity effect lung volumes. The reference values of lung volume and capacities were calculated previously and those studies played pivotal role in establishing the fact that air volume capacities measured in an individual fall within a wide range among healthy persons of same age, gender and height but with different ethnicity. The objective of this study was to evaluate the changes in vital capacity in with height and gender. Methods: This cross-sectional study included 74 male students in the Department of Physiology, Liaquat University of Medical and Health Sciences, Jamshoro during January-March, 2014. The volunteers were divided into 2 groups of height ‰¤167.4 cm and >167.4 cm. The volunteers’ height was measured in cm. Vital capacity of the subjects was measured using standard protocol. Mean±SD of age, height and vital capacity were calculated. Results: Mean vital capacity in students with height >167.4 cm was higher than average vital capacity of students with height ‰¤167.4 cm. It might be due to the increased surface area of the lungs in relation with increasing height. Conclusions: There are variations in vital capacity of individuals in relation to their heights, within the same ethnic and age groups. Keywords:Height, Vital Capacity, Pulmonary Function Test, Spirometry Background: Vital Capacity (VC) is defined as a change in volume of lung after maximal inspiration followed by maximal expiration is called Vital Capacity of lungs. It is the sum of tidal volume, inspiratory reserve volume and expiratory reserve volume. Vital capacity of normal adults ranges between 3 to 5 litres. A number of physiological factors like age, gender, height and ethnicity effect lung volumes. The reference values of lung volume and capacities were calculated previously and those studies played pivotal role in establishing the fact that air volume capacities measured in an individual fall within a wide range among healthy persons of same age, gender and height but with different ethnicity. The objective of this study was to evaluate the changes in vital capacity in with height and gender. Methods: This cross-sectional study included 74 male students in the Department of Physiology, Liaquat University of Medical and Health Sciences, Jamshoro during January-March, 2014. The volunteers were divided into 2 groups of height ‰¤167.4 cm and >167.4 cm. The volunteers’ height was measured in cm. Vital capacity of the subjects was measured using standard protocol. Mean±SD of age, height and vital capacity were calculated. Results: Mean vital capacity in students with height >167.4 cm was higher than average vital capacity of students with height ‰¤167.4 cm. It might be due to the increased surface area of the lungs in relation with increasing height. Conclusions: There are variations in vital capacity of individuals in relation to their heights, within the same ethnic and age groups. Keywords: Height, Vital Capacity, Pulmonary Function Test, Spirometry